The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1177/1470593118767725
|View full text |Cite
|
Sign up to set email alerts
|

Materializing digital collecting: An extended view of digital materiality

Abstract: If digital objects are abundant and ubiquitous, why should consumers pay for, much less collect them? The qualities of digital code present numerous challenges for collecting, yet digital collecting can and does occur. We explore the role of companies in constructing digital consumption objects that encourage and support collecting behaviours, identifying material configuration techniques that materialize these objects as elusive and authentic. Such techniques, we argue, may facilitate those pleasures of colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 98 publications
1
72
0
4
Order By: Relevance
“…Previous research has shown that many contemporary consumers share a desire of collecting experiences (Keinan and Kivetz, 2011; Mardon and Belk, 2018). In this desire to multiply the experiences, consumers tend to look for extraordinary, extreme, and original experiences, from skydiving (Celsi et al, 1993) and river rafting (Arnould and Price, 1993) to the grueling adventure challenge Tough Mudder (Scott et al, 2017) or they participate in the Burning Man Festival (Kozinets, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that many contemporary consumers share a desire of collecting experiences (Keinan and Kivetz, 2011; Mardon and Belk, 2018). In this desire to multiply the experiences, consumers tend to look for extraordinary, extreme, and original experiences, from skydiving (Celsi et al, 1993) and river rafting (Arnould and Price, 1993) to the grueling adventure challenge Tough Mudder (Scott et al, 2017) or they participate in the Burning Man Festival (Kozinets, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, connectivity enables new attributes and these include interoperability (e.g., Bharadwaj, El Sawy, Pavlou, and Venkatraman, 2013; Kallinikos et al, 2013; Porter and Heppelmann, 2014, 2015; Yoo et al, 2012), pervasiveness (e.g., Kolb, 2008; Kolb, Caza, and Collins, 2012; Wajcman and Rose, 2011), speed (e.g., Bharadwaj et al, 2013; Lazer and Friedman, 2007; Siggelkow and Rivkin, 2005; Svahn and Henfridsson, 2012), synchronization (e.g., Angwin and Vaara, 2005; Chatterjee, Segars, and Watson, 2006; Overby, 2008; Porter and Heppelmann, 2014), accessibility/transferability (e.g., Cross, Laseter, Parker, and Velasquez, 2006; Kallinikos et al, 2013; Lee and Berente, 2012; Leonardi and Bailey, 2008; Matusik and Mickel, 2011; Mazmanian, 2013; Mazmanian, Orlikowski, and Yates, 2013; Zittrain, 2006, 2008; Zhang, Yoo, Wattal, Zhang, and Kulathinal, 2014), and ubiquity (e.g., Iansiti and Lakhani, 2014; Kolb, 2008; Mardon and Belk, 2018; Sørensen and Landau, 2015; Wajcman and Rose, 2011). 6 Figure 2 provides a succinct visual representation of these properties in a holistic fashion.…”
Section: The Digital Transformation Of Search and Recombination: New mentioning
confidence: 99%
“…They also introduced unique features like stats that change as games are played, mystery packs in which it is uncertain which cards will appear, and limited editions and cards that are only available during limited time periods. These innovative adaptations have resulted in a $330 million market for Topps virtual cards (Mardon and Belk 2018).…”
Section: Russell Belkmentioning
confidence: 99%